PATHOPHYSIOLOGICAL ROLE OF FEVER - Kopchuk, T.G.; Rohovyy, Yu.Ye. (World of Medicine and Biology, 2012)
In the article the modern literary data about the pathophysiological role of fever as a typical pathological process, that is characterized by displacement of the “set point” of thermoregulation on the higher level of the regulation of body temperature under the influence of the pyrogenic substances and always takes place in three stages, according to which the temperature curve consists of three parts too, are defined.